Hole transport material and preparation method, solar cell and preparation method

By using hole transport materials with core-shell structures in perovskite solar cells and using metal oxide nanomaterials as cores and SAMs materials as shells, the problems of insufficient stability and efficiency of hole transport materials in the prior art are solved. Achieve higher solar cell efficiency and stability.

CN119053162BActive Publication Date: 2025-02-18TRINA SOLAR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411535712.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Among existing perovskite solar cells, the stability and structural efficiency of hole transport materials are low, resulting in insufficient efficiency and stability of solar cells.

Method used

A hole transport material with a core-shell structure is used, which is coated with a metal oxide nanomaterial with a hole transport function as the core, and is coated with a first SAMs material with a hole transport function as the shell.

Benefits of technology

The hole transmission capability and photothermal stability of solar cells are improved, the direct contact between metal oxide nanomaterials and perovskite material layers is avoided, and the efficiency and stability of solar cells are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119053162B_ABST
    Figure CN119053162B_ABST
Patent Text Reader

Abstract

The present invention relates to a hole transport material and a preparation method, a solar cell and a preparation method. The hole transport material is a core-shell structure having a core and a shell layer, wherein the core is a metal oxide nanomaterial having a hole transport function, and the shell layer is a first SAMs material having a hole transport function. The hole transport material and its preparation method use a metal oxide nanomaterial having a hole transport function as a core, have good hole transport ability, and have good photothermal stability. The core is coated with a first SAMs material having a hole transport function, and the first SAMs material can selectively transport holes, and can avoid the metal oxide nanomaterial having a hole transport function from contacting with a perovskite material layer and reacting, thereby avoiding the decomposition of the perovskite material, and effectively improving the efficiency and stability of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a hole transport material and a preparation method thereof, a solar cell and a preparation method thereof. Background Art

[0002] Organic and inorganic metal halide perovskite materials have the advantages of excellent photoelectric performance and low cost, and are suitable as light-absorbing layers of solar cells. In addition, the band gap of perovskite materials is adjustable, and they can be stacked with other photovoltaic materials such as crystalline silicon to form stacked solar cells, thereby achieving higher photoelectric conversion efficiency.

[0003] Perovskite solar cells usually have a hole transport layer between the TCO substrate and the perovskite light absorption layer. Traditionally used hole transport materials mainly include metal oxides such as nickel oxide, polymers such as PEDOT:PSS, self-assembled monolayers (SAMs), etc. Among them, metal oxide hole transport materials have good hole transport capabilities, but they will undergo redox reactions when in contact with perovskite materials, resulting in poor stability of solar cells. Organic polymer hole transport materials will decompose under long-term light and have poor stability. SAMs-type hole transport materials can transport holes. By setting a layer of SAMs-type hole transport materials between the metal oxide hole transport layer and the perovskite material layer, direct contact between the metal oxide hole transport layer and the perovskite material layer can be avoided, thereby improving stability. However, the structural efficiency and stability of SAMs-type hole transport materials deposited on metal oxides still need to be improved. Summary of the invention

[0004] Based on this, it is necessary to provide a hole transport material and a preparation method, a solar cell and a preparation method to improve the efficiency and stability of the solar cell.

[0005] The first aspect of the present invention is to provide a hole transport material, the scheme is as follows:

[0006] A hole transport material has a core-shell structure with a core and a shell layer, wherein the core is a metal oxide nanomaterial with a hole transport function, and the shell layer is a first SAMs material with a hole transport function.

[0007] In one embodiment, the first SAMs material includes a first functional group and a first anchoring group, the first SAMs material is bonded to the metal oxide nanomaterial through the first anchoring group, and the first SAMs material has a dipole moment, and the direction of the dipole moment is from the first functional group to the first anchoring group.

[0008] In one embodiment, the first anchoring group includes at least one of phosphonic acid, carboxylic acid, cyanoacetic acid, and cyanophosphonic acid.

[0009] In one embodiment, the first functional group includes at least one of carbazole, dibenzocarbazole, and acridine.

[0010] In one embodiment, the first SAMs material having a hole transport function is selected from at least one of the compounds having structures represented by the following general formulas (1) to (3):

[0011] (1)

[0012] (2)

[0013] (3);

[0014] Among them, R 1 , R 2 , R 9 , R 10 are independently selected from -H, C1~C4 alkyl, C1~C4 alkoxy, benzene ring or -X, where X is a halogen atom; R 3 , R 5 , R 11 Independently selected from C1~C4 alkyl; R 7 , R 8 Independently selected from -H, -CH 3 , -C 2 H 5 ; R 4 , R 6 , R 12 Independently selected from phosphonic acid, carboxylic acid, cyanoacetic acid or cyanophosphonic acid.

[0015] In one embodiment, the metal oxide nanomaterial includes ITO, FTO, ICO, NiO w , CuO 2 ,CuO,CuAlO 2 、CuCrO 2 , WO 3 、MoO x , VO y CrO z One or more of the following, wherein w is 1-2, x is 0.5-3, y is 1-2.5, and z is 1-3.

[0016] In one embodiment, the core is a nanoparticle, a nanosheet, a nanowire or a nanotube.

[0017] In one embodiment, the core is a nanoparticle with a particle size of 1 nm to 200 nm.

[0018] In one embodiment, the core is a nanosheet with a maximum width of 1 nm to 200 nm and a thickness of 1 nm to 50 nm.

[0019] In one embodiment, the core is a nanowire with a radial size of 1 nm to 50 nm and an aspect ratio of (4 to 200):1.

[0020] In one embodiment, the core is a nanotube with a radial size of 1 nm to 50 nm and an aspect ratio of (4 to 200):1.

[0021] The second aspect of the present invention is to provide a method for preparing the hole transport material of any one of the above embodiments, the scheme is as follows:

[0022] A method for preparing a hole transport material comprises the following steps:

[0023] Obtaining the metal oxide nanomaterial having a hole transport function and the first SAMs material having a hole transport function, and dispersing them together in a solvent to obtain a mixed solution;

[0024] Drying and annealing the mixed solution to prepare a hole transport material with a core-shell structure;

[0025] The core of the hole transport material is the metal oxide nanomaterial, and the shell is the first SAMs material.

[0026] The third aspect of the present invention is to provide a solar cell, the scheme is as follows:

[0027] A solar cell comprising:

[0028] a first electrode layer;

[0029] A first hole transport layer, disposed on the first electrode layer, the first hole transport layer comprising a hole transport material, the hole transport material being a core-shell structure having a core and a shell layer, the core being a metal oxide nanomaterial having a hole transport function, and the shell layer being a first SAMs material having a hole transport function;

[0030] a perovskite light absorption layer, disposed on a side of the first hole transport layer away from the first electrode layer;

[0031] and a second electrode layer, which is arranged on a side of the perovskite light absorption layer away from the first hole transport layer.

[0032] In one embodiment, the solar cell further comprises:

[0033] The second hole transport layer is arranged between the first electrode layer and the first hole transport layer, and the second hole transport layer is a second SAMs material having a hole transport function.

[0034] In one embodiment, the second SAMs material includes a second functional group and a second anchoring group, the second SAMs material is bonded to the first electrode layer through the second anchoring group, and the second SAMs material has a dipole moment, and the direction of the dipole moment is from the second functional group to the second anchoring group.

[0035] The fourth aspect of the present invention is to provide a method for preparing a solar cell, the scheme is as follows:

[0036] A method for preparing a solar cell, in one embodiment, comprises the following steps:

[0037] providing a first electrode layer;

[0038] forming the first hole transport layer on the first electrode layer, wherein the first hole transport layer comprises a hole transport material, wherein the hole transport material is a core-shell structure having a core and a shell layer, wherein the core is a metal oxide nanomaterial having a hole transport function, and the shell layer is a first SAMs material having a hole transport function;

[0039] forming a perovskite light absorption layer on a side of the first hole transport layer away from the first electrode layer;

[0040] A second electrode layer is formed on a side of the perovskite light absorbing layer away from the first hole transport layer.

[0041] In one embodiment, before forming the first hole transport layer, the preparation method further comprises the following steps:

[0042] A second hole transport layer is formed on the first electrode layer, and the second hole transport layer is a second SAMs material having a hole transport function.

[0043] Compared with the traditional scheme, the above hole transport material and preparation method, solar cell and preparation method have the following beneficial effects:

[0044] The above-mentioned hole transport material and its preparation method have a metal oxide nanomaterial with hole transport function as the core, have good hole transport ability, and have good photothermal stability. The core is coated with a first SAMs material with hole transport function. The first SAMs material can selectively transport holes and can avoid the metal oxide nanomaterial from contacting and reacting with the perovskite material layer, avoid the decomposition of the perovskite material, and effectively improve the efficiency and stability of solar cells.

[0045] The solar cell and the preparation method thereof adopt the hole transport material as the hole transport layer, and can obtain corresponding beneficial effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] FIG1 is a schematic structural diagram of a hole transport material according to an embodiment;

[0047] FIG2 is a schematic structural diagram of a solar cell according to an embodiment;

[0048] FIG3 is a schematic structural diagram of a first hole transport layer, a second hole transport layer and a first electrode layer in the solar cell shown in FIG2 ;

[0049] FIG. 4 is a schematic structural diagram of a solar cell according to another embodiment. DETAILED DESCRIPTION

[0050] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0052] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0053] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0054] The term "alkyl" refers to a saturated hydrocarbon containing primary carbon atoms, secondary carbon atoms, tertiary carbon atoms, quaternary carbon atoms, or a combination thereof. Phrases containing this term, such as "C 1 ~C 4 "Alkyl" refers to an alkyl group containing 1 to 4 carbon atoms, each occurrence of which can be independently C 1 Alkyl, C 2 Alkyl, C 3 Alkyl, C 4 Alkyl. The alkyl group may be straight chain or branched. Suitable examples include, but are not limited to, methyl (Me, -CH 3 ), ethyl (Et, -CH 2 CH 3 ), 1-propyl (n-Pr, n-propyl, -CH 2 CH 2 CH 3 ), 2-propyl (i-Pr, i-propyl, -CH (CH 3 ) 2 ), 1-butyl (n-Bu, n-butyl, -CH 2 CH 2 CH 2 CH 3 ), 2-methyl-1-propyl (i-Bu, i-butyl, -CH 2 CH(CH 3 ) 2 ), 2-butyl (s-Bu, s-butyl, -CH (CH 3 )CH 2 CH3 ), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH 3 ) 3 ).

[0055] The term "alkoxy" refers to a group having an -O-alkyl group, i.e., an alkyl group as defined above attached via an oxygen atom to a parent core structure. Phrases containing this term, such as "C 1 ~C 4 "Alkoxy" means that the alkyl part contains 1 to 4 carbon atoms, each occurrence can be independently C 1 Alkoxy, C 4 Alkoxy, C 5 Alkoxy. Alkoxy can be straight chain or branched. Suitable examples include, but are not limited to, methoxy (-O-CH 3 or -OMe), ethoxy (-O-CH 2 CH 3 or -OEt) and tert-butyloxy (-OC(CH 3 ) 3 or -OtBu).

[0056] The present invention provides a hole transport material.

[0057] As shown in FIG1 , the hole transport material of one embodiment is a core-shell structure, having a core 11 and a shell 12 coated on the core 11. The core 11 is a metal oxide nanomaterial having a hole transport function, and the shell 12 is a first SAMs material having a hole transport function.

[0058] Nanostructured metal oxides can be deposited on substrates by solution methods, which have simple production processes and low costs. When nanostructured metal oxides are coated on substrates, it cannot be guaranteed that the SAMs-type hole transport materials subsequently deposited thereon can well cover the surface of the nanostructures and the gaps between the nanostructures. This makes the subsequently deposited perovskite materials still in contact with the metal oxides that are not modified by SAMs.

[0059] The above-mentioned hole transport material has a metal oxide nanomaterial with hole transport function as the core 11, has good hole transport ability, and has good photothermal stability. The core 11 is coated with a first SAMs material with hole transport function. The first SAMs material can selectively transport holes and can avoid the metal oxide nanomaterial from contacting and reacting with the perovskite material layer, avoid the decomposition of the perovskite material, and effectively improve the efficiency and stability of the solar cell 100.

[0060] In the core-shell structure, the core 11 is a nanostructure. Optionally, the core 11 may be, but is not limited to, nanoparticles, nanosheets, nanowires, and nanotubes.

[0061] In FIG1 , the core 11 is a nanoparticle. The nanoparticle is a spherical particle, including particles that are approximately spherical. The particle size of the nanoparticle is, for example, 1 nm to 200 nm.

[0062] The maximum width of the nanosheet is, for example, 1 nm to 200 nm, and the thickness of the nanosheet is, for example, 1 nm to 50 nm.

[0063] The radial dimension of the nanowire is, for example, 1 nm to 50 nm. The aspect ratio of the nanowire is, for example, (4 to 200):1.

[0064] The radial dimension of the nanotube is, for example, 1 nm to 50 nm. The aspect ratio of the nanotube is, for example, (4 to 200):1.

[0065] Among them, the metal oxide nanomaterials with hole transport function can be but are not limited to indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium cerium oxide (ICO), NiO w (w is 1~2), CuO 2 ,CuO,CuAlO 2 、CuCrO 2 , WO 3 、MoO x (x is 0.5~3), VO y (y is 1~2.5), CrO z (z is 1~3) One or more.

[0066] The first SAMs material includes a first functional group and a first anchoring group. The first SAMs material is bonded to the metal oxide nanomaterial of the core 11 through the first anchoring group. The first SAMs material has a dipole moment, and the direction of the dipole moment is from the first functional group to the first anchoring group, so that holes can be selectively transmitted.

[0067] Optionally, the first anchoring group may be but is not limited to at least one of phosphonic acid, carboxylic acid, cyanoacetic acid, and cyanophosphonic acid. The first anchoring group enables the first SAMs material to have good self-assembly ability, can form a good bond with the substrate, and enhances the interaction with the substrate.

[0068] Optionally, the first functional group includes, but is not limited to, at least one of carbazole, dibenzocarbazole, and acridine.

[0069] In some examples, the first SAMs material is selected from at least one of the compounds having molecular structures shown in the following general formulas (1) to (3):

[0070] (1)

[0071] (2)

[0072] (3);

[0073] Among them, R 1 , R 2 , R 9 , R 10 are independently selected from -H, C1~C4 alkyl, C1~C4 alkoxy, benzene ring or -X, where X is a halogen atom; R 3 , R 5 , R 11 Independently selected from C1~C4 alkyl; R 7 , R 8 Independently selected from -H, -CH 3 , -C 2 H 5 ; R 4 , R 6 , R 12 Independently selected from phosphonic acid, carboxylic acid, cyanoacetic acid or cyanophosphonic acid.

[0074] Furthermore, R 1 , R 2 , R 9 , R 10 Independently selected from -OCH 3 or -X, X is a halogen atom. Further, R 1 , R 2 , R 9 , R 10 Independently selected from -OCH 3 or -Br. The above groups match the structural energy level of the main group, making the material have better hole extraction ability.

[0075] Furthermore, R 3 , R 5 , R 11 Independently selected from -C 2 H 4 -or-C 4 H 8 -. The above groups match the structural energy levels of the main groups, making the material have better hole extraction ability.

[0076] Furthermore, R 7 , R 8 Independently selected from -H or -CH 3 . Furthermore, R 7 , R 8 -CH3 The structural energy levels of the above groups match those of the main groups, which makes the material have better hole extraction ability.

[0077] Furthermore, R 4 , R 6 , R 12 Independently selected from phosphonic acid or cyanophosphonic acid. The above groups have multiple active sites, can enhance the interaction with the substrate, and have a better anchoring effect.

[0078] For example, the first SAMs material can be, but is not limited to, [6-(9H-carbazol-9-yl)hexyl]phosphonic acid (6PACz), [1-(9H-carbazol-9-yl)methyl]phosphonic acid (1PACz), [2-(9H-carbazol-9-yl)ethyl]phosphonic acid (2PACz), [3-(9H-carbazol-9-yl)propyl]phosphonic acid (3PACz), [4-(9H-carbazol-9-yl)butyl]phosphonic acid (4PACz), [8-(9H-carbazol-9-yl)octyl]phosphonic acid (8PACz), [4-(9H-9'-phenyl-3,3'-dicarbazol-9-yl)butyl]phosphonic acid (4PABCz), [2-(9H-9'-phenyl-3,3'-dicarbazol-9-yl)butyl]phosphonic acid (4PABCz), [4-(9H-9'-phenyl-3,3'-dicarbazol-9-yl)butyl]phosphonic acid (4PABCz), [2-(9H-9'-phenyl-3,3'-dicarbazol-9-yl)propyl]phosphonic acid (3PACz), [4-(9H-9'-phenyl-3,3'-dicarbazol-9-yl)butyl]phosphonic acid (4PABCz), [2-(9H-9'-phenyl-3,3'-dicarbazol-9 -yl)ethyl]phosphonic acid (2PABCz), [4-(diphenylamino)phenyl)propyl]phosphonic acid (TPA-3PA), [4-(diphenylamino)phenyl)ethyl]phosphonic acid (TPA-2PA), [6-(3,6-dibromo-9H-carbazole-9-yl)hexyl]phosphonic acid (2Br-6PACz), [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-2PACz), [3-(3,6-dimethyl-9H-carbazole-9-yl)propyl]phosphonic acid (Me-3PACz), [6-(3,6-dimethyl-9H-carbazole-9-yl)hexyl]phosphonic acid (Me-6PACz), [8-(3,6-dimethyl-9H-carbazole-9-yl) )octyl]phosphonic acid (Me-8PACz), [1-(3,6-di-tert-butyl-9H-carbazole-9-yl)methyl]phosphonic acid (tBu-1PACz), [2-(3,6-di-tert-butyl-9H-carbazole-9-yl)ethyl]phosphonic acid (tBu-2PACz), [3-(3,6-di-tert-butyl-9H-carbazole-9-yl)propyl]phosphonic acid (tBu-3PACz), [4-(3,6-di-tert-butyl-9H-carbazole-9-yl)butyl]phosphonic acid (tBu-4PACz), [6-(3,6-di-tert-butyl-9H-carbazole-9-yl)hexyl]phosphonic acid (tBu-1PACz), [8-(3,6-di-tert-butyl-9H-carbazole-9-yl)octyl]phosphonic acid Ph-1PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)methyl]phosphonic acid (Ph-2PACz), [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Ph-3PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)propyl]phosphonic acid (Ph-4PACz), [6-(3,6-diphenyl-9H-carbazole-9-yl)hexyl]phosphonic acid (Ph-6PACz), [8-(3,6-diphenyl-9H-carbazole-9-yl)octyl]phosphonic acid (Ph-8PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid (Ph-4PACz), [6-(3,6-diphenyl-9H-carbazole-9-yl)hexyl]phosphonic acid (Ph-6PACz), [8-(3,6-diphenyl-9H-carbazole-9-yl)octyl]phosphonic acid (Ph-8PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid (Ph-8PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)hexyl]phosphonic acid (Ph-8PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)octyl]phosphonic acid (Ph-8PACz).6-dibromo-9H-carbazole-9-yl)butyl]phosphonic acid (2Br-4PACz), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid (4PADCB), [2-(7H-dibenzocarbazole-7-yl)ethyl]phosphonic acid (2PADCB), [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid (MeO-6PACz), [4-(N,N-di(4-methoxyphenylamino)phenyl)propyl]phosphonic acid (MeO-TPA-3PA), [2-(10H-phenoxazine-10-yl)ethyl]phosphonic acid (2PAPXZ), [1-(3,6-dimethyl-9H-carbazole-9-yl)methyl]phosphonic acid ( Me-1PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]phosphonic acid (2Br-4PADMAc), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid, [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]phosphonic acid. ,

[0079] The phosphonic acid group in the above compound examples may also be replaced by a carboxylic acid group, a cyanoacetic acid group or a cyanophosphonic acid group, which will not be listed here one by one.

[0080] Furthermore, the present invention also provides a hole transport material according to any of the above examples.

[0081] Step S110, a method for preparing a hole transport material according to an embodiment, comprises the following steps:

[0082] A metal oxide nanomaterial with a hole transport function and a first SAMs material with a hole transport function are obtained, and are dispersed in a solvent to obtain a mixed solution.

[0083] Step S120, drying the mixed solution to obtain a dry product.

[0084] Step S130, annealing the dried product.

[0085] In step S110, the solvent may be, but is not limited to, one or more of isopropanol, ethanol, chlorobenzene, n-butanol, ethyl acetate, acetone, benzyl chloroformate, methyl nylonate, acetonitrile, tetramethylsilane, N,N-dimethylformamide, dimethyl sulfoxide, and acetonitrile, for example, a mixed solvent of ethanol and DMF in a volume ratio of 98:2.

[0086] In step S120 , the drying process may be performed by evaporating the solvent, and the evaporation temperature is, for example, 50° C. to 300° C., and further, for example, 80° C. to 150° C.

[0087] In step S130, the temperature of the annealing treatment is, for example, 25° C. to 200° C. The time of the annealing treatment is, for example, 1 min to 100 min. In a specific example, the temperature of the annealing treatment is 100° C., and the time of the annealing treatment is 15 min.

[0088] Furthermore, the present invention also provides a solar cell 100 .

[0089] As shown in FIG. 2 , a solar cell 100 according to an embodiment includes a first electrode layer 110 , a first hole transport layer 120 , a perovskite light absorbing layer 130 , and a second electrode layer 140 .

[0090] The first hole transport layer 120 is disposed on the first electrode layer 110. The first hole transport layer 120 includes any hole transport material of the above examples. The perovskite light absorbing layer 130 is disposed on a side of the first hole transport layer 120 away from the first electrode layer 110. The second electrode layer 140 is disposed on a side of the perovskite light absorbing layer 130 away from the first hole transport layer 120.

[0091] Optionally, the material of the first electrode layer 110 may be a conductive metal oxide, for example, one or more of but not limited to indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), indium-doped zinc oxide (IZO), fluorine-doped tin oxide (FTO), indium tungsten oxide (IWO), indium cerium oxide (ICO) and the like.

[0092] The perovskite light absorbing layer 130 includes a perovskite material ABX 3 . Wherein, A is a monovalent cation, including but not limited to one or more of cesium ion, rubidium ion, potassium ion, methylamine ion, formamidine ion, methylenediamine ion, benzamidine cation and guanidinium cation. B is a divalent cation, including but not limited to one or more of lead ion, copper ion, zinc ion, gallium ion, tin ion and calcium ion. X is a monovalent anion, including but not limited to one or more of fluoride ion, chloride ion, bromide ion, iodide ion, thiocyanate ion, tetrafluoroborate ion, hexafluorophosphate ion, formate ion and acetate ion.

[0093] In some examples, the thickness of the perovskite light absorbing layer 130 is 20 nm to 2000 nm. Further, in some examples, the thickness of the perovskite light absorbing layer 130 is 100 nm to 1500 nm. Further, in some examples, the thickness of the perovskite light absorbing layer 130 is 30 nm to 600 nm. In some specific examples, the thickness of the perovskite light absorbing layer 130 is 20 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, 2000 nm, etc.

[0094] Optionally, the material of the second electrode layer 140 may be, but is not limited to, a metal material, such as one or more of Au, Ag, Cu, and the like.

[0095] As shown in Figures 2 and 3, in some examples, the solar cell 100 further includes a second hole transport layer 150. The second hole transport layer 150 is disposed between the first electrode layer 110 and the first hole transport layer 120. The second hole transport layer 150 is a second SAMs material having a hole transport function.

[0096] The above-mentioned solar cell 100 further sets a second hole transport layer 150 between the first electrode layer 110 and the first hole transport layer 120. The second hole transport layer 150 is a second SAMs material, which can improve the hole transport effect and more effectively avoid potential contact between the perovskite light absorption layer 130 and the first electrode layer 110, thereby improving the stability of the solar cell 100.

[0097] The second SAMs material includes a second functional group and a second anchoring group. The second SAMs material is bonded to the substrate, such as the first electrode layer 110, through the second anchoring group. The second SAMs material has a dipole moment, and the direction of the dipole moment is from the second functional group to the second anchoring group, so that holes can be selectively transported.

[0098] Optionally, the second anchoring group can be but not limited to at least one of phosphonic acid, carboxylic acid, cyanoacetic acid, and cyanophosphonic acid. The second anchoring group enables the second SAMs material to have good self-assembly ability, can form a good bond with the substrate, and enhances the interaction with the substrate.

[0099] Optionally, the second functional group may be, but is not limited to, at least one of carbazole, dibenzocarbazole, and acridine.

[0100] The second SAMs material may also be selected from at least one of the compounds having the molecular structures represented by the above general formulas (1) to (3). Specific examples of the second SAMs material may also be the examples given for the first SAMs material.

[0101] It should be noted that, in the same solar cell 100 , the first SAMs material and the second SAMs material may be the same or different.

[0102] As shown in FIG. 2 , in some examples, the solar cell 100 further includes an electron transport layer 160 . The electron transport layer 160 is disposed between the perovskite light absorbing layer 130 and the second electrode layer 140 .

[0103] Optionally, the material of the electron transport layer 160 may be, but is not limited to, ZnO (zinc oxide), SnO 2 (tin oxide), TiO 2 (TiO2), SrTiO 3 (Strontium titanate), Zn 2 SnO 4 (Zinc stannate), ZrO 2 (Zirconium dioxide), Al 2 O 3 (aluminum oxide), WO 3 (Tungsten trioxide), CeO x (cesium oxide), CdS (cadmium sulfide), CdSe (cadmium selenide), BaSnO 3 (barium stannate), Nb 2 O 5 (niobium pentoxide), C 60 (Fullerene), C 70 , PCBM (fullerene derivative) or more.

[0104] In some examples, the thickness of the electron transport layer 160 is 1 nm to 30 nm. Further, in some examples, the thickness of the electron transport layer 160 is 5 nm to 20 nm. In some specific examples, the thickness of the electron transport layer 160 is 2 nm, 5 nm, 8 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 27 nm, 29 nm, 30 nm, etc.

[0105] The solar cell may be a single-layer perovskite cell or a tandem cell, wherein the tandem cell may be, for example, a perovskite / crystalline silicon tandem cell, a full perovskite tandem cell, a perovskite / organic tandem cell, a perovskite / CIGS tandem cell, a perovskite / CdTe tandem cell, a perovskite / GaAs tandem cell, etc.

[0106] For example, the solar cell 200 shown in FIG4 is a perovskite / crystalline silicon stacked cell, which includes a transparent electrode layer 201, a first doped layer 202, a first amorphous silicon layer 203, a single crystal silicon substrate 204, a second amorphous silicon layer 205, a second doped layer 206, a first electrode layer 207, a second hole transport layer 208, a first hole transport layer 209, a perovskite light absorption layer 210, an electron transport layer 211, a second electrode layer 212, and an anti-reflection layer 213. A first grid line 214 is disposed on the anti-reflection layer 213, and a second grid line 215 is disposed on the transparent electrode layer 201.

[0107] It is understandable that the solar cell may also have other functional layers, such as a hole blocking layer, an electron blocking layer, etc. When implementing the present invention, those skilled in the art may supplement the structural features of the solar cell based on the aforementioned technical features as needed.

[0108] Furthermore, the present invention also provides a method for preparing any of the solar cells described above.

[0109] A method for preparing a solar cell according to an embodiment of the present invention comprises the following steps:

[0110] Step S210: providing a first electrode layer.

[0111] Step S220: forming a first hole transport layer on the first electrode layer.

[0112] Step S230: forming a perovskite light absorption layer on a side of the first hole transport layer away from the first electrode layer.

[0113] Step S240: forming a second electrode layer on a side of the perovskite light absorbing layer away from the first hole transport layer.

[0114] In some examples, before forming the first hole transport layer (step S220), the method for preparing a solar cell further includes the following steps:

[0115] A second hole transport layer is formed on the first electrode layer, wherein the second hole transport layer is a second SAMs material.

[0116] In this example, the first hole transport layer is formed on a side of the second hole transport layer away from the first electrode layer.

[0117] In some examples, before forming the second electrode layer (step S240), the method for preparing a solar cell further includes the following steps:

[0118] An electron transport layer is formed on a side of the perovskite light absorbing layer away from the first hole transport layer.

[0119] Optionally, the preparation process of the above-mentioned first hole transport layer, perovskite light absorption layer, second hole transport layer and electron transport layer can be but not limited to evaporation, magnetron sputtering, atomic layer deposition, electrochemical deposition, molecular beam evaporation, dip coating, spin coating, blade coating, slit coating, rod coating and inkjet printing, etc.

[0120] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods and does not limit the protection scope of the present invention.

[0121] Example 1

[0122] The method for preparing a solar cell provided in this embodiment comprises the following steps:

[0123] Step 1, obtain ITO conductive glass with a size of 2.5 cm×2.5 cm, clean and dry it, and then treat it in an ultraviolet and ozone environment for 20 minutes to obtain a first electrode layer.

[0124] Step 2, prepare hole transport material. Take the SAMs material [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) and dissolve it in a mixed solvent containing ethanol and DMF with a volume ratio of 98:2 to obtain a Me-4PACz solution with a concentration of 0.5 mg / mL. Take nickel oxide nanoparticles with a particle size of 5-10 nm and add them to the Me-4PACz solution. Add 20 mg of nickel oxide nanoparticles to 1 mL of Me-4PACz solution to obtain a mixed solution.

[0125] After the mixture was sealed, it was ultrasonically bathed for 10 minutes and then left to stand for 5 hours. Subsequently, the mixture was spread in a petri dish and the solvent was evaporated at 100°C. After complete drying, it was annealed at 100°C for 15 minutes, and the product was washed twice with ethanol and dried to obtain a hole transport material.

[0126] Step 3, dissolve the above hole transport material in ethanol at a concentration of 15 mg / mL, and take 50 μL and drop it on the first electrode layer, spin coat it at 3000 rpm for 20 s, and then anneal it at 100 °C for 10 min to obtain a hole transport layer.

[0127] Step 4: prepare a perovskite precursor solution, using DMF and DMSO in a volume ratio of 4:1 as solvent, and mix CsI, FAI, PbI 2 and PbBr 2According to the concentration of Pb being 1.5 M, it was added to the solvent, and 60 mg / mL of methyl ammonium chloride (MACl) was added and stirred for 6 h to obtain a perovskite precursor solution.

[0128] In a nitrogen glove box, the perovskite precursor solution was dropped onto the hole transport layer, and the solution was first spin-coated at 500 rpm for 5 s, then at 4000 rpm for 50 s, and then at 5000 rpm for 40 s. Chlorobenzene was flushed onto the substrate surface, and then annealed at 120 °C for 20 min to prepare the perovskite material FA. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 ) 3 , and obtain a perovskite light absorbing layer.

[0129] Step 5: Prepare a 1,3-propylenediamine hydroiodide solution, using isopropanol as the solvent at a concentration of 0.5 mg / mL. In a nitrogen glove box, drop the 1,3-propylenediamine hydroiodide solution onto the perovskite light absorption layer, spin-coat at 4000 rpm for 30 s, and then anneal at 100 °C for 2 min to obtain a passivation layer.

[0130] Step 6: C60 with a thickness of 30 nm is deposited on the passivation layer by a thermal evaporation process to obtain an electron transport layer.

[0131] Step 7: Deposit BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) with a thickness of 6 nm on the electron transport layer by a thermal evaporation process to obtain a hole blocking layer.

[0132] Step 8: Deposit metal Ag with a thickness of 200 nm on the hole blocking layer by thermal evaporation to obtain a second electrode layer.

[0133] Example 2

[0134] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 1, except that in step 2, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) is used instead of Me-4PACz.

[0135] Example 3

[0136] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 1, except that in step 2, [2-(7H-dibenzocarbazole-7-yl)ethyl]phosphonic acid (2PADCB) is used instead of Me-4PACz.

[0137] Example 4

[0138] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 1, except that in step 2, [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]carboxylic acid is used instead of Me-4PACz.

[0139] Example 5

[0140] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 1, except that in step 2, [6-(9H-carbazole-9-yl)hexyl]cyanophosphonic acid is used instead of Me-4PACz.

[0141] Example 6

[0142] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 1, except that in step 2, [1-(9H-carbazole-9-yl)methyl]cyanoacetic acid is used instead of Me-4PACz.

[0143] Example 7

[0144] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 1, except that in step 2, copper peroxide (CuO 2 ) to replace nickel oxide.

[0145] Example 8

[0146] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 1, except that, in step 2, copper oxide (CuO) is used instead of nickel oxide.

[0147] Example 9

[0148] The method for preparing a solar cell provided in this embodiment comprises the following steps:

[0149] Step 1, obtain ITO conductive glass with a size of 2.5 cm×2.5 cm, clean and dry it, and then treat it in an ultraviolet and ozone environment for 20 minutes to obtain a first electrode layer.

[0150] Step 2: Take the SAMs material Me-4PACz and dissolve it in a mixed solvent containing ethanol and DMF in a volume ratio of 98:2 to obtain a Me-4PACz solution with a concentration of 0.5 mg / mL. The Me-4PACz solution is dropped onto the first electrode layer, allowed to stand for 20 seconds, and then spin-coated at a speed of 4000 rpm for 20 seconds, and then annealed at 100°C for 10 minutes to form a hole transport layer 1.

[0151] Step 3, take nickel oxide nanoparticles with a particle size of 5-10 nm and add them to the Me-4PACz solution prepared in step 2, and add 20 mg of nickel oxide nanoparticles to 1 mL of Me-4PACz solution to obtain a mixed solution.

[0152] After the mixture was sealed, it was ultrasonically bathed for 10 minutes and then left to stand for 5 hours. Subsequently, the mixture was spread in a petri dish and the solvent was evaporated at 100°C. After complete drying, it was annealed at 100°C for 15 minutes, and the product was washed twice with ethanol and dried to obtain a hole transport material.

[0153] Step 4, dissolve the above hole transport material in ethanol at a concentration of 15 mg / mL, take 50 μL and drop it on the hole transport layer 1, spin coat it at a speed of 3000 rpm for 20 s, and then anneal it at 100 °C for 10 min to form a hole transport layer 2.

[0154] Step 5: prepare a perovskite precursor solution, using DMF and DMSO in a volume ratio of 4:1 as solvent, and mix CsI, FAI, PbI 2 and PbBr 2 According to the concentration of Pb being 1.5 M, it was added to the solvent, and 60 mg / mL of methyl ammonium chloride (MACl) was added and stirred for 6 h to form a perovskite precursor solution.

[0155] In a nitrogen glove box, the perovskite precursor solution was dropped onto the hole transport layer 2, and the solution was first spin-coated at 500 rpm for 5 s, then at 4000 rpm for 50 s, and then at 5000 rpm for 40 s. Chlorobenzene was flushed onto the substrate surface, and then annealed at 120 °C for 20 min to prepare the perovskite material FA. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 ) 3 , forming a perovskite light absorption layer.

[0156] Step 6: Prepare a 1,3-propylenediamine hydroiodide solution, using isopropanol as the solvent at a concentration of 0.5 mg / mL. In a nitrogen glove box, drop the 1,3-propylenediamine hydroiodide solution onto the perovskite light absorption layer, spin-coat at 4000 rpm for 30 s, and then anneal at 100 °C for 2 min to form a passivation layer.

[0157] Step 7: C60 with a thickness of 30 nm is deposited on the passivation layer by a thermal evaporation process to form an electron transport layer.

[0158] Step 8: Deposit BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) with a thickness of 6 nm on the electron transport layer by a thermal evaporation process to form a hole blocking layer.

[0159] Step 9: Deposit metal Ag with a thickness of 200 nm on the hole blocking layer by thermal evaporation to form a second electrode layer.

[0160] Example 10

[0161] The method for preparing the solar cell provided in this embodiment is substantially the same as that in embodiment 9, except that in step 2, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) is used instead of Me-4PACz.

[0162] Embodiment 11

[0163] The preparation method of the solar cell provided in this embodiment is basically the same as that of Embodiment 9, except that in step 2, [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid (Ph-4PACz) is used instead of Me-4PACz.

[0164] Comparative Example 1

[0165] The preparation method of the solar cell of this comparative example comprises the following steps:

[0166] Step 1, obtain ITO conductive glass with a size of 2.5 cm×2.5 cm, clean and dry it, and then treat it in an ultraviolet and ozone environment for 20 minutes to obtain a first electrode layer.

[0167] Step 2: Add nickel oxide nanoparticles with a particle size of 5-10 nm to deionized water, add 20 mg of nickel oxide nanoparticles to every 1 mL of deionized water, and ultrasonicate for 10 min to obtain a nickel oxide solution. Add 50 μL of the nickel oxide solution dropwise onto the first electrode layer, spin-coat at 3000 rpm for 20 s, and then anneal at 100 °C for 10 min to form a hole transport layer 1.

[0168] Step 3, dissolve the SAMs material Me-4PACz in a mixed solvent containing ethanol and DMF in a volume ratio of 98:2 to obtain a Me-4PACz solution with a concentration of 0.5 mg / mL. Take 50 μL Me-4PACz solution and drop it on the hole transport layer 1, spin-coat it at 4000 rpm for 20 s, and then anneal it at 100 °C for 10 min to form a hole transport layer 2.

[0169] Step 4: prepare a perovskite precursor solution, using DMF and DMSO in a volume ratio of 4:1 as solvent, and mix CsI, FAI, PbI2 and PbBr 2 According to the concentration of Pb being 1.5 M, it was added to the solvent, and 60 mg / mL of methyl ammonium chloride (MACl) was added and stirred for 6 h to form a perovskite precursor solution.

[0170] In a nitrogen glove box, the perovskite precursor solution was dropped onto the hole transport layer 2, and the solution was first spin-coated at 500 rpm for 5 s, then at 4000 rpm for 50 s, and then at 5000 rpm for 40 s. Chlorobenzene was flushed onto the substrate surface, and then annealed at 120 °C for 20 min to prepare the perovskite material FA. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 ) 3 , forming a perovskite light absorption layer.

[0171] Step 5: Prepare a 1,3-propylenediamine hydroiodide solution, using isopropanol as the solvent at a concentration of 0.5 mg / mL. In a nitrogen glove box, drop the 1,3-propylenediamine hydroiodide solution onto the perovskite light absorption layer, spin-coat at 4000 rpm for 30 s, and then anneal at 100 °C for 2 min to form a passivation layer.

[0172] Step 6: C60 with a thickness of 30 nm is deposited on the passivation layer by a thermal evaporation process to form an electron transport layer.

[0173] Step 7: Deposit BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) with a thickness of 6 nm on the electron transport layer by a thermal evaporation process to form a hole blocking layer.

[0174] Step 8: Deposit metal Ag with a thickness of 200 nm on the hole blocking layer by thermal evaporation to form a second electrode layer.

[0175] The performance of the solar cell prepared above was tested under standard test conditions, i.e., the air quality was AM1.5 G and the light intensity was 100 mW / cm 2 , the temperature is 25 ℃, the test results are shown in Table 1.

[0176] Comparative Example 2

[0177] The preparation method of the solar cell of this comparative example is basically the same as that of comparative example 1, except that step 3 is not performed, that is, only the hole transport layer 1 is prepared, and the hole transport layer 2 is not prepared.

[0178] Comparative Example 3

[0179] The preparation method of the solar cell in this comparative example is basically the same as that in comparative example 1, except that in step 2, CuO 2 Replaces nickel oxide.

[0180] Comparative Example 4

[0181] The method for preparing the solar cell provided in this embodiment is substantially the same as that of Comparative Example 1, except that in step 2, CuO is used instead of nickel oxide.

[0182] Table 1 Performance parameters of solar cells tested under standard test conditions

[0183]

[0184] The solar cell prepared above was placed in an environment of 85°C for 1000 h for aging treatment, and the performance of the solar cell after aging was tested. The test results are shown in Table 2.

[0185] Table 2 Performance parameters of solar cells after aging

[0186]

[0187] The hole transport material used in Examples 1 to 11 has a metal oxide nanomaterial as the core, and the core is coated with a SAMs material having a hole transport function, and the prepared solar cells have high short-circuit current, open-circuit voltage, fill factor, photoelectric conversion efficiency and other properties. As shown in Table 1, compared with Comparative Example 1, the open-circuit voltage, fill factor and photoelectric conversion efficiency of the solar cell in Example 1 are all improved to a certain extent.

[0188] It can be seen from the results in Table 2 that after aging treatment, the electrical properties of the solar cell have all declined. One of the reasons is that the self-assembled monolayer as the first hole transport layer has the risk of failure under long-term high temperature. After the self-assembled monolayer fails, the metal oxide in the lower layer contacts the perovskite material and then undergoes redox reaction, which reduces the stability of the solar cell.

[0189] It can be seen from the results in Table 2 that the degree of decline in electrical performance of Example 1 is significantly reduced compared to that of Comparative Example 1. After aging treatment, the short-circuit current of Example 1 decreased by 0.15%, the open-circuit voltage decreased by 0.88%, the fill factor decreased by 1.42%, and the photoelectric conversion efficiency decreased by 2.44%. The short-circuit current of Comparative Example 1 decreased by 4.47%, the open-circuit voltage decreased by 5.08%, the fill factor decreased by 8.17%, and the photoelectric conversion efficiency decreased by 16.71%. This shows that the use of SAMs materials with hole transport function to coat metal oxide nanomaterials to form a hole transport material as a hole transport layer can better avoid the metal oxide nanomaterial from contacting and reacting with the perovskite material layer, avoid the decomposition of the perovskite material, and effectively improve the efficiency and stability of solar cells.

[0190] The difference between Example 1 and Example 7 and Example 8 is that the metal oxide hole transport materials are different. From the results in Table 1 and Table 2, it can be seen that when the metal oxide hole transport material is nickel oxide (Example 1), the battery electrical performance is significantly better than that of copper peroxide (Example 7) and copper oxide (Example 8).

[0191] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0192] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A solar cell, characterized in that: include: The first electrode layer is made of conductive metal oxide; A first hole transport layer, disposed on the first electrode layer, the first hole transport layer comprising a hole transport material, the hole transport material being a core-shell structure having a core and a shell layer, the core being a metal oxide nanomaterial having a hole transport function, and the shell layer being a first SAMs material having a hole transport function; A second hole transport layer is provided between the first electrode layer and the first hole transport layer, the second hole transport layer is a second SAMs material having a hole transport function, the second SAMs material comprises a second functional group and a second anchoring group, the second SAMs material is bonded to the first electrode layer through the second anchoring group, the second SAMs material has a dipole moment, and the direction of the dipole moment is a direction from the second functional group to the second anchoring group; a perovskite light absorption layer, disposed on a side of the first hole transport layer away from the first electrode layer; as well as The second electrode layer is arranged on a side of the perovskite light absorbing layer away from the first hole transporting layer.

2. The solar cell according to claim 1, wherein: The first SAMs material includes a first functional group and a first anchoring group. The first SAMs material is bonded to the metal oxide nanomaterial via the first anchoring group. The first SAMs material has a dipole moment, and the direction of the dipole moment is from the first functional group to the first anchoring group.

3. The solar cell according to claim 2, characterized in that The first anchoring group comprises at least one of phosphonic acid, carboxylic acid, cyanoacetic acid, and cyanophosphonic acid; and / or The first functional group includes at least one of carbazole, dibenzocarbazole and acridine.

4. The solar cell according to claim 1, wherein: The first SAMs material is selected from at least one of the compounds having structures represented by the following general formulas (1) to (3): (1)、 (2)、 (3); Among them, R1, R2, R9, R 10 are independently selected from -H, C1~C4 alkyl, C1~C4 alkoxy, -OCH3, benzene ring or -X, X is a halogen atom; R3, R5, R 11 are independently selected from C1~C4 alkyl; R7 and R8 are independently selected from -H, -CH3, -C2H5; R4, R6, R 12 Independently selected from phosphonic acid, carboxylic acid, cyanoacetic acid or cyanophosphonic acid.

5. The solar cell according to claim 1, wherein: The metal oxide nanomaterial is selected from ITO, FTO, ICO, NiO w , CuO2, CuO, CuAlO2, CuCrO2, WO3, MoO x , VO y CrO z One or more of the following, wherein w is 1-2, x is 0.5-3, y is 1-2.5, and z is 1-3.

6. The solar cell according to any one of claims 1 to 5, characterized in that The core is a nanoparticle, a nanosheet, a nanowire or a nanotube.

7. The solar cell according to claim 6, characterized in that The core is a nanoparticle with a particle size of 1 nm to 200 nm; or The core is a nanosheet with a maximum width of 1 nm to 200 nm and a thickness of 1 nm to 50 nm; or The core is a nanowire with a radial size of 1 nm to 50 nm and an aspect ratio of (4 to 200):1; or The inner core is a nanotube with a radial size of 1 nm to 50 nm and an aspect ratio of (4 to 200):

1.

8. A method for preparing a solar cell, characterized in that: The following steps are involved: Providing a first electrode layer, the material of which is a conductive metal oxide; forming a first hole transport layer on the first electrode layer, wherein the first hole transport layer comprises a hole transport material, wherein the hole transport material is a core-shell structure having a core and a shell layer, wherein the core is a metal oxide nanomaterial having a hole transport function, and the shell layer is a first SAMs material having a hole transport function; forming a perovskite light absorption layer on a side of the first hole transport layer away from the first electrode layer; forming a second electrode layer on a side of the perovskite light absorbing layer away from the first hole transport layer; Before forming the first hole transport layer, the preparation method further comprises the following steps: A second hole transport layer is formed on the first electrode layer, the second hole transport layer is a second SAMs material with a hole transport function, the second SAMs material includes a second functional group and a second anchoring group, the second SAMs material is bonded to the first electrode layer through the second anchoring group, the second SAMs material has a dipole moment, and the direction of the dipole moment is from the second functional group to the second anchoring group.

Citation Information

Patent Citations

  • Photoelectric device and preparation method thereof, photovoltaic module and photovoltaic system

    CN117177595A

  • Hole transport material and preparation method thereof, hole transport layer and preparation method thereof, solar cell, solar cell module and electric equipment

    CN118742056A